The quiet eye and tasks demands: Do tougher shots need a quieter eye? - Walters-Symons, R.; Wilson, M. R.; Klostermann, A.; Vine, S. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The Quiet Eye (QE; Vickers 1996) has been shown to underpin successful performance, differentiating both expertise (inter-individual) and proficiency (intra-individual), with experts and successful attempts characterised by longer QE durations. The QE is proposed to reflect the time needed to organise and fine tune the parameters of movement (e.g. force and direction). In order to examine this prediction and build upon previous research we experimentally manipulated the difficulty of a golf putting task; we hypothesised that if the QE is related to motor programming then a more difficult task should be associated with longer QE durations. 33 golfers (M age= 21.16, SD= 3.98) with an average handicap of 6.5 (SD= 6.02) performed putts in 4 conditions of increasing difficulty. We manipulated the length of the golf putt (short-4ft, long-8ft) and the contact point of the putter head (large-1.7cm, small-0.5cm,) giving increasingly difficult putting conditions of short-large [1], short-small [2], long-large [3] and long-small [4]. We measured performance (radial error from hole in cm) and QE (in ms) for 10 putts in each condition. A repeated measures ANOVA was performed on the performance and QE data. The performance data suggest that we were successful in increasing the difficulty of the task (F (3,93) = 26.46. p = .000), with the best performance in condition [1] (8.57cm), followed by [2] (9.10cm) followed by [3] (16.11cm) and finally the worst performance was in condition [4] (23.40cm). The QE data suggest that, in keeping with our hypothesis, the QE was lengthened as task difficulty increased (F (3,87) = 11.91, p = .043). The QE was shortest in condition [1] (1787.85ms) and increased to condition [2] (1939.78ms) and condition [3] (2076.51ms), with the longest QE in condition [4] (2164.08ms). More detailed analysis of the QE reveal that it was the proportion of the QE that occurred before movement initiation (pre-QE) which increased with shot difficulty, rather than the proportion that occurred during the swing (Online-QE; see Vine et al., 2013). Results support the notion that more complex tasks are associated with a longer QE duration, specifically participants appear to spend longer fixating the target prior to movement. This likely reflects the time needed to process visual information gathered in a preperformance routine, to inhibit external distraction, and to pre-programme the increasingly difficult parameters of the movement.